2017
DOI: 10.2337/dc16-2175
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Properties of Biomarkers GDF-15, NTproBNP, and hs-TnT for Morbidity and Mortality in Patients With Type 2 Diabetes With Nephropathy

Abstract: Biomarkers GDF-15, NTproBNP, and hs-TnT associate independently with renal risk, whereas NTproBNP independently predicts cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…The dynamic change of the plasma level of NT-proBNP is correlated with the clinical prognosis of patients with acute decompensated heart failure when they are discharged (10). Meanwhile, it is the independent risk factor for cardiovascular events (11). This study also found the correlation between the plasm level of mtDNA and NT-proBNP after CPB.…”
Section: Discussionsupporting
confidence: 62%
“…The dynamic change of the plasma level of NT-proBNP is correlated with the clinical prognosis of patients with acute decompensated heart failure when they are discharged (10). Meanwhile, it is the independent risk factor for cardiovascular events (11). This study also found the correlation between the plasm level of mtDNA and NT-proBNP after CPB.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, our top "core sSASP" biomarker candidates have been identified as disease biomarkers in human studies. For example, human cohort studies have reported GDF15 as a biomarker of cardiovascular disease, cardiovascular and cancer mortality and morbidity, renal disease, and all-cause mortality independent of cardiovascular mortality [60][61][62][63][64][65][66], as well as a driver of senescence-associated colon cancer metastasis [67]. Additionally, two of the top core sSASP proteins identified by an unbiased k-means clustering algorithm-STC1 and MMP1 (Fig 7B and 7C)-were reported as significant aging biomarkers [48].…”
Section: Discussionmentioning
confidence: 99%
“…Of these markers, the authors noted that 20 proteins (9.2%) are present in the originally-defined SASP (Coppé et al, 2008 (Figure 6A). In addition to aging, various large cohort studies identified GDF15 as a biomarker of cardiovascular disease, cardiovascular and cancer mortality and morbidity, renal disease, and all-cause mortality independent of cardiovascular mortality (Bidadkosh et al, 2017;Daniels et al, 2011;Ho et al, 2012Ho et al, , 2013Rohatgi et al, 2012;Wallentin et al, 2013;Wollert et al, 2017).…”
Section: The Sasp Contains Potential Aging and Disease Biomarkersmentioning
confidence: 99%